Micropolítica e gestão regionalizada da saúde: estudo de caso no colegiado de gestão da 4ª Região Sanitária do Estado do Rio Grande do Sul - Barrios, Sueli Terezinha Goi (2009)
This dissertation regards the research of the micro politics of work, at the "Regional Management School" (Colegiado de Gestão Regional), also known as COGERE. This work's main goal is to analyze the technologies used in the protocols of management and decision making by managers at COGERE 4th Health Region. This study aims to contribute to the knowledge of health management and its practice. The theoretic framework of this dissertation is based on the analysis of the Brazilian Health Reconstruction, the legislation of the "Single Health System" (Sistema Único de Saúde, also known as SUS), the health system work protocols and the association of the fields of care and management. This study is also based on Emerson Elias Merhy's and Michel Foucault's work. The methodology uses the qualitative approach, and the investigative approach is the case study, because we are dealing with the analysis of a SUS decision-making institution, which is the COGERE 4th Health Region, located in the south of Brazil. The subjects researched were the staff of this management school and the data was surveyed through interviews, observation and document analysis. The findings of this study allow us to say that the technologies used by decisionmaking managers at COGERE, are most likely "light-hard" and "hard" when bound to the standards, ordinances, rules, contracts, technical knowledge systematized and structured, over the "light" technologies, that were supposed to be predominant at this place, where the theoretical assumptions are relationships among people, co-management, dialogue, sharing and the collective construction of the management politic process and health political organizations, at the 4th Health Region, located in the south of Brazil.